Direct oxidation of cyclohexane to adipic acid by a WFeCoO(OH) catalyst: role of bronsted acidity and oxygen vacancies - Vernekar, Dnyanesh; Dayyan, Mohammad; Ratha, Satyajit; Rode, V, Chandrashekhar; Haider, M. Ali; Khan, Tuhin Suvra; Jagadeesan, Dinesh (ACS Catalysis, 2021)
This work reports the catalytic activity of the trimetallic mixed-metal oxyhydroxide WFeCoO(OH) for the direct oxidation of cyclohexane to adipic acid (AA) without the use of concentrated HNO3. WFeCoO(OH) displayed a 40% conversion of cyclohexane and a 67% selectivity to AA under relatively milder conditions of temperature (90 degrees C) and pressure (1 atm). Experimental evidence confirmed the presence of acidic, basic, and redox sites on WFeCoO(OH). The detailed investigation revealed that doping W in the Co-FeO(OH) matrix increased the amount of surface lattice oxygen (OS-L) and caused a significant surge in acidity (5.1 mmol/g). The calculated deprotonation energy of WFeCoO(OH) was 1434 kJ/mol, and the trend in acidity was WCoO(OH) < WFeCoO(OH) < FeCoO(OH) similar to CoO(OH). Energy calculations showed that WFeCoO(OH) had a high propensity to generate oxygen vacancies by the loss of either a water molecule or an oxygen atom (-132.2 or -140.9 kJ/mol, respectively). Basicity was generated due to the presence of conjugate pairs of the surface hydroxyl groups. The combined action of the trifunctional acidic, basic, and redox-active metal centers along with the oxygen vacancies was responsible for the enhanced catalytic performance.
Keywords: Adipic Acid; deprotonation energy; metal oxyhydroxides; multifunctional catalysts; oxygen vacancies

Direct conversion of methane to formic acid over Au-Fe-NaZSM-5 at ambient pressure using H2O2 - Kumar, Pawan; Ahangar, Iqra; Kesarwani, Srishti; Urkude, Rajashri; Patil, Nita A. R.; Niphadkar, Prashant; Bokade, Vijay V.; Haider, M. Ali; Vinod, C. P. (Catalysis Science & Technology, 2026)
Direct conversion of methane to value-added products is a long-standing challenge. This report presents the one-step conversion of methane to oxygenates using H2O2 as an oxidant over an Au and Fe supported on NaZSM-5 (0.1Au0.1FeNZ) catalyst, which produces 4264 mu mol of oxygenates with 89% selectivity toward formic acid at 10 bar and 60 degrees C within 30 min in a batch process. The catalyst also produces 26.5 mu mol of oxygenates with 70% selectivity for formic acid at atmospheric pressure and 80 degrees C in a continuous flow process over 9 h of reaction time, making it the first report of such a process. The synergistic interaction of Au and Fe, with the crucial role of Na ions in the zeolite framework in driving the reaction, is revealed through various characterization tools like TEM, XPS, and XAS. Theoretical studies elucidate the active sites responsible for lowering the activation barrier for the crucial C-H activation step. Thus, the catalyst enables the conversion of methane into formic acid with high activity and selectivity, offering new possibilities for harnessing this potent greenhouse gas under process-friendly conditions that were previously unexplored.